The complete mitochondrial genome of Citrus sinensis. Issue 2 (3rd July 2018) - Yu, Fengwen; Bi, Changwei; Wang, Xuelin; Qian, Xin; Ye, Ning
Abstract: Citrus sinensis is an important agricultural product with huge economic value. In this study, we report the complete mitochondrial (mt) genome sequence of Citrus sinensis for the first time. Our assembly of the Citrus sinensis mt genome resulted in a final sequence of 640, 906 bp in length which contains 63 genes. Phylogenetic analysis showed that Citrus sinensis was closely related to Brassica napus and Arabidopsis thaliana, which also belong to malvids. The complete mt genome will facilitate further genetic studies of Citrus sinensis .